Hooley, T., Sultana, R. G., Thomsen, R. (eds.): Career Guidance for Social Justice: Contesting Neoliberalism - Helena Košťálová (Karolinum Press, 2019)
Book review: Hooley, T., Sultana, R. G., & Thomsen, R. (eds.): Career Guidance for Social Justice: Contesting Neoliberalism. New York: Routledge, 2018, 271 s.